Pelatihan Dan Pendampingan Penyusunan Media Pembelajaran Berbasisi Digital Bagi Guru-Guru PPKn Di Kabupaten Belu - Thomas Kemil Masi; Leonard Lobo; Marsi D. S. Bani; Petrus Ly; Fredik Lambertus Kollo (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Atambuah 2 Public Middle School is located in Belu Regency. Middle School, High School/Vocational School teachers in Belu Regency carry out their teaching duties well with the available facilities and are active in activities to develop teachers' academic potential, but teaching skills training has not been carried out for users of digital learning media in schools, so this has an impact on student interest and motivation. in learning. Reading this situation, the Undana PPKn Study Program PKM Team will carry out Training and Assistance activities in Preparing Digital-based Learning Media for PPKn Teachers in the Border Areas of Belu Regency. By providing training and assistance in preparing digital-based learning media for middle school, high school/vocational education PPKn teachers in Belu Regency, teachers can develop professionalism in learning and improve the quality of education for students. So that the main objective of this community service activity program can be achieved, namely in the form of Assistance in Preparing Digital-Based Learning Media for PPKn Teachers in the Border Areas of Belu Regency, apart from being able to improve teacher skills, it can also increase student motivation and interest in learning. The design and production of learning media based on the Canva for Education application is carried out by (1) tutorials on designing and producing learning media using Canva for Education; (2) assistance in designing and producing learning media using Canva for education; (3) assignment to design and produce learning media using Canva for education; (4) demonstration of learning media products using Canva for education.